Effect of Ni60-WC on Properties of NiCrAl Coating. (October 2020) - He, Binfeng; Ye, Fangxia; Liu, Mingxia
Abstract: Ni60-WC reinforced NiCrAl coatings were prepared on the TC4 alloy by laser cladding technique with different mixed powders: 95%NiCrAl-5%Ni60-WC, 85%NiCrAl-15%Ni60-WC, 75%NiCrAl-25%Ni60-WC (wt.%). The microstructure, phases compositions, microhardness, wear properties were studied. The results showed that the mainly consists of dendrites and bulk like compounds crystal and some of flower-like microstructure formed. The XRD results indicated TiC, VC metalloceramics, Cr0.2Ti0.8C, NiTi2, Ni2W4C and AlFe3C intermetallic compounds generated. The microhardness of the coatings are 881HV0.3, 778HV0.3 and 788HV0.3, respectively. Compared with the substrate hardness about 200HV0.3, the hardness of coatings have been improved significant. The friction coefficient of coatings are 0.35, 0.42, and 0.42, respectively, and the wear rates of the coatings are 3.86×10-7mm3N-1m-1, 4.51×10-7mm3N-1m-1 and 4.34×10-7mm3N-1m-1, respectively.